GENETIC INFLUENCE ON AGE OF MENOPAUSE IN THE LONG LIFE FAMILY STUDY AND HEALTH AND RETIREMENT STUDY. (11th November 2018) - Bae, H; Gurinovich, A; Sweigart, B; Lunetta, K; Murabito, J; Andersen, S; Perls, T; Sebastiani, P
Abstract: Several studies have observed that women who are able to naturally have children later in life tend to live longer. We hypothesize that the evolutionary pressure to extend the period of time in which women can bear children and therefore have the opportunity to have more of them could be a mechanism for the selection of genetic variants that slow aging and decrease risk for age-related diseases. While previous genetic studies have sought to discover genetic variants associated with age of menopause (AOM) in normally aging populations, our analysis aims to discover genetic variants that are associated with AOM in participants of the Long Life Family Study (LLFS), a cohort of families enriched for longevity, and combine the results with the Health and Retirement Study (HRS) in a meta-analysis. We meta-analyzed results from analysis of 1.5M single nucleotide polymorphisms (SNP) data of 4, 457 women in the LLFS and HRS combined. We used Cox proportional hazard regression to model AOM accounting for censoring. We then sought replication using results from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium 2015 meta-analysis of AOM. rs16991615 reached genome-wide significance and was previously found to be associated with an 11 month older AOM. There were also statistically suggestive novel SNPs on the X chromosome discovered in the LLFS data. Specifically, we found intronic variants of UTP14A, whose encoded proteins have anti-apoptotic role in tumor cells.